Public knowledge and understanding of Alzheimer´s disease in Iceland - Katrín Eyjólfsdóttir 1992- (2016)
Public knowledge of Alzheimer´s Disease (AD) is vital. With research and increased awareness of AD it is effectively possible to reduce the discomfort of patients and their families and improve services to patients within the health care system. The aim of this study was assess general public knowledge in Iceland about AD and to examine factors that affect this knowledge. The sample was 1,002 Icelanders from 18-80 years old. General knowledge levels of AD were assessed via the Alzheimer´s Disease Knowledge Scale (ADKS). Results of the study revealed that: 1) females scored higher on the ADKS than males 2) having had information on AD had a stronger impact on knowledge of AD than having had a personal experience of knowing someone who has/has had AD; and 3) persons with a university degree did better on the ADKS than those who had secondary education or less. Keywords: Alzheimer´s disease, public awareness, education, experience Þekking á Alzheimer sjúkdómnum er mikilvæg. Með rannsóknum og aukinni vitund á Alzheimer er á árangursríkan hátt hægt að draga úr vanlíðan sjúklinga og aðstandenda ásamt því að bæta þjónustu við sjúklinga innan heilbrigðiskerfisins. Markmið þessarar rannsóknar var að meta almenna þekkingu Íslendinga á Alzheimer sjúkdómnum og að skoða þá þætti sem hafa áhrif á þekkinguna. Þýðið samanstóð af 1002 Íslendingum á aldrinum 18-80 ára. Þekking almennings var metin með Alzheimer´s Disease Knowledge Scale (ADKS). Niðurstöður rannsóknarinnar leiddu í ljós að: 1) konur skoruðu hærra á ADKS heldur en karlar 2) það að hafa fengið fræðslu um Alzheimer hafði meiri áhrif á þekkingu á sjúkdómnum heldur en að hafa persónulega þekkt einhvern sem er eða var með Alzheimer; og 3) einstaklingar með háskólagráðu gekk betur á ADKS en þeir sem voru með framhaldsskóla menntun eða minna. Lykilorð: Alzheimer sjúkdómur, almenn þekking, menntun, reynsla